Global awareness of Japanese high school students - Hiromi Ishimori, (Universiti Kebangsaan Malaysia, 2009)
As globalisation continues to be a main determinant on all aspects of life, education for international understanding has never been more critical. Starting with the view that Japanese students possess lower awareness about other cultures as compared to their Western counterpart, it is essential to rejuvenate Japanese students into a more global-minded direction. With this goal in mind, this study places its focus on analysing current Japanese high school students' attitudes and perception on intercultural relationship. This study utilised a survey method. The sample comprised one thousand two hundred and seven (n = 1,207) second year Japanese high school students from ten different high schools across Japan, stretching from Hokkaido to Kyushu. The study found that Japanese youngsters possess biases with regards to Western and non-Western cultures. Their prejudice may be influenced by mass media. Therefore, effective strategies need to be implemented so that Japanese students will ultimately desire to make friends with foreigners regardless of race, culture, language, colour, and religion.